2019
DOI: 10.1111/evj.13112
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of repeated oral dosing of acetaminophen in adult horses

Abstract: Summary Background There are no published studies on the pharmacokinetics of acetaminophen at the dosage used clinically (20 mg/kg), nor has the safety of multiple doses in horses been investigated. Objective Define the pharmacokinetic parameters of oral acetaminophen at 20 mg/kg in adult horses as a single dose, and twice daily for 14 days to assess the safety of multiple dosing. Study design Pharmacokinetic study, multiple dose safety study. Methods Eight healthy Thoroughbred geldings were given acetaminophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 32 publications
5
51
8
Order By: Relevance
“…Anecdotally, use of acetaminophen as an analgesic in horses is increasing (Bowen et al, 2020) and the authors have used it as part of a multimodal approach in other cases with perceived positive effects. Acetaminophen has been shown to be safe in horses at the dose used in this report (Mercer et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Anecdotally, use of acetaminophen as an analgesic in horses is increasing (Bowen et al, 2020) and the authors have used it as part of a multimodal approach in other cases with perceived positive effects. Acetaminophen has been shown to be safe in horses at the dose used in this report (Mercer et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…Acetaminophen has been shown to be safe in horses at the dose used in this report (Mercer et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study using domestic animal species showed that paracetamol is highly proteinbound in horses, which delays drug clearance, and it is also highly bioavailable compared with dogs (Neirinckx et al 2010). Further, a recent study determined that the drug halflife is significantly extended following multi-dose treatment regimens (Mercer et al 2020). Thus, it should not be assumed that paracetamol pharmacokinetics can be extrapolated from other species, and further study in horses is warranted.…”
Section: Anti-inflammatories and Paracetamolmentioning
confidence: 99%
“…Thus, it should not be assumed that paracetamol pharmacokinetics can be extrapolated from other species, and further study in horses is warranted. However, the limited data available suggest that paracetamol may be a safe and effective analgesic for laminitis pain (West et al 2011;Mercer et al 2020).…”
Section: Anti-inflammatories and Paracetamolmentioning
confidence: 99%
“…It is commonly used in human medicine where it is frequently combined with other non‐steroidal anti‐inflammatory drugs to provide a greater analgesic and anti‐inflammatory effect. Mercer et al 8 described the pharmacokinetics and safety of repeated oral dosing with Acetaminophen in eight adult horses using a 20 mg/kg, twice daily dose for 14 days. Collected pharmacological data demonstrated that concentrations increased above the proposed minimum therapeutic level in humans for only 2 hours post‐administration.…”
mentioning
confidence: 99%